Identifying determinants of food security using panel data analysis: Evidence from Maghreb countries - Guerrache Mohamed; Fayçal Chiad; Menacer Abdesslam; Belkacem Omar; Mujeeb Saif Mohsen Al Absy (Economies, 2024)
Countries and international bodies are focusing on agriculture as a route to achieving sustainable food security. Hence, the aim of this study is to examine the determinants of food security. It investigates the effects of gross domestic product deflator (GDPD), rural population, arable area, agricultural workers, farmers, agricultural exports, and agricultural imports on agricultural performance, which is a metric of food security. This study uses time lapse data models of a sample from the group of Maghreb states, namely Libya, Tunisia, Algeria, Morocco, and Mauritania, for the 2003-2018 period. All these data were collected from the statistical reports of the Arab Organization for Agricultural Development. The results provide evidence of the significant positive impacts of gross domestic product, arable areas, and agricultural exports on the agricultural sector's performance, which results in achieving food security. However, the results indicate that the rural population and the number of workers in the agricultural sector have a significantly negative relationship with agricultural sector performance. In terms of agricultural imports, the results do not show a relationship between agricultural imports and agricultural sector performance. To the best of the researchers' knowledge, this is the first study conducted in the Maghreb states, including five countries. This study alerts policymakers to issues regarding the importance of having effective policies that could enhance the performance of agricultural production to achieve food security in the Maghreb states. Policymakers must improve the investment climate in North African countries to encourage investors to enter the agricultural sector.
Keywords: 330; agricultural performance; arable area; food security; gross domestic product; Maghreb; panel data